Left Atrial Strain: Crucial Cardiac Navigator in Practice - Shantanu P Sengupta; Ashish Agarwal (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2023)
Left ventricular (LV) diastolic pressure estimation is essential for characterization of heart failure. Despite extensive research and the availability of numerous metrics, the assessment of LV diastolic pressures both at rest and after exertion has been challenging. Left atrial strain assessment by echocardiography has recently shown promise in correlating with LV end-diastolic pressure. This review provides information about this novel technology.